A Low-Noise, Low-Offset CMOS Readout IC for Amperometric Biosensors - Manu Chilukuri; Shanthala Lakshminarayana; Hyusim Park; Chenyun Pan; Hoon-Ju Chung; Sungyong Jung (IEEE Access)
Electrochemical sensing systems are crucial in driving forward the development of biosensors that is indispensable for health monitoring. In this work, a compact, low-noise, and low-offset CMOS readout circuit has been proposed for amperometric biosensors. It comprises of a transimpedance amplifier, a sample and hold buffer, bias generator, and an on-chip clock generator. A two-step measurement method is introduced to enhance the noise performance and linearity of the signal path. Additionally, a faster and energy-efficient analog autozero scheme is proposed to mitigate amplifier offset and sampled noise, which is a crucial aspect when detecting current in the range of nano-ampere. The proposed readout circuit attains notable specifications, including an input-referred noise of 0.16 pArms, an input-referred offset of 137 nV, an accuracy level of 2%, and a power consumption of 48 $μ $ A from a 1.8V supply. It is designed using a 0.18 $μ $ m CMOS process and occupies a compact size of 1.47 mm2. This circuit is compatible with a screen-printed electrode sensor and can seamlessly integrate into a flexible printed circuit board. Such integration facilitates its inclusion as a component within a wearable health monitoring system, ensuring expeditious and precise estimation of analyte concentration.